2015
DOI: 10.1158/1940-6207.capr-14-0454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Short-term 1,25-Dihydroxyvitamin D3 on the Chemopreventive Efficacy of Erlotinib against Oral Cancer

Abstract: Activation of the epidermal growth factor receptor (EGFR) pathway is an early event in head and neck carcinogenesis. As a result, targeting EGFR for chemoprevention of head and neck squamous cell carcinomas (HNSCC) has received considerable attention. In the present study, we examined the impact of 1,25(OH)2D3, the active metabolite of the nutritional supplement vitamin D on the chemopreventive efficacy of the EGFR inhibitor, erlotinib, against HNSCC. Experimental studies were conducted in patient derived xeno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…We utilized noninvasive T2-weighted MRI (T2W-MRI) to longitudinally monitor the effects of 4NQO exposure in old and young C57BL/6 mice. In a previous study, T2W-MRI of 6- to 8-wk-old mice that were not exposed to the carcinogen 4NQO did not show any evidence of oral or extraoral neoplasms (Bothwell et al 2015). Similarly, MRI examination performed on naïve mice of different ages without intervention (i.e., 4NQO exposure) did not show any evidence of oral neoplasms (Appendix Figs.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…We utilized noninvasive T2-weighted MRI (T2W-MRI) to longitudinally monitor the effects of 4NQO exposure in old and young C57BL/6 mice. In a previous study, T2W-MRI of 6- to 8-wk-old mice that were not exposed to the carcinogen 4NQO did not show any evidence of oral or extraoral neoplasms (Bothwell et al 2015). Similarly, MRI examination performed on naïve mice of different ages without intervention (i.e., 4NQO exposure) did not show any evidence of oral neoplasms (Appendix Figs.…”
Section: Resultsmentioning
confidence: 82%
“…The carcinogen 4NQO was dissolved in propylene glycol at 4 mg/mL and diluted in autoclaved water to a final concentration of 100 μg/mL (Bothwell et al 2015). Young and old C57BL/6 mice were exposed to 4NQO in drinking water for 16 wk (Fig.…”
Section: Nqo Oral Carcinogenesis Modelmentioning
confidence: 99%
“…4NQO is a water-soluble chemical that leads to the malignant transformation and development of invasive cancer through intracellular oxidative stress and the formation of DNA adducts [14,15]. Studies by us and others have shown that 4NQO-induced tumors share histopathologic and molecular features of human OSCC and the model can serve as a useful platform to investigate the activity of chemopreventive agents against the spectrum of oral carcinogenesis [16][17][18]. Although disease progression in this model can be accelerated by simultaneous treatment with tumor promoters (e.g., ethanol), the requirement of chronic administration of the carcinogen (16-26 weeks) limits the widespread use of this model for therapeutic studies [19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lainey et al [ 39 ] showed that either of the aforementioned EGFR inhibitors, together with 1,25(OH) 2 D 3 , induces markers and processes associated with differentiation, such as CD11b and CD14 expression, cell cycle arrest, apoptosis, and NADPH oxidase activity. Moreover, a recent study investigating the potential use of erlotinib together with 1,25(OH) 2 D 3 in head and neck squamous cell carcinoma utilized in vivo models to demonstrate augmented reduction of tumor growth in the combination regimen compared to single drug treatments [ 40 ]. Further analyses illustrated that this combination reduces phosphorylation of Akt (S473) and EGFR (Y1092) [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study investigating the potential use of erlotinib together with 1,25(OH) 2 D 3 in head and neck squamous cell carcinoma utilized in vivo models to demonstrate augmented reduction of tumor growth in the combination regimen compared to single drug treatments [ 40 ]. Further analyses illustrated that this combination reduces phosphorylation of Akt (S473) and EGFR (Y1092) [ 40 ].…”
Section: Introductionmentioning
confidence: 99%